Global integration along historic pathways: Vienna and Munich in the changing financial geography of Europe. (October 2014) - Zademach, Hans-Martin; Musil, Robert
Taking the two second-tier financial centres Munich and Vienna as illustrative cases, this paper empirically evaluates the extent to which the restructuring of the banking and insurance industry and the emergence of new financial agents calls for a reappraisal of the geography of European finance against longer-term developments. Conceptually, the paper adopts an evolutionary perspective that conceives inter- and intra-sectoral corporate takeovers and mergers and the rise of the private equity industry as driving forces for diversification/specification of financial centres. The paper traces the historic origins and long-term evolution of financial services in Munich and Vienna and then provides a twofold investigation of new empirical data: first a static investigation of the location networks of the 50 largest private equity firms and the 30 most important European banks; and second a network analysis of 493 merger and acquisition transactions in the European banking and insurance industries between 1997 and 2009. The study reveals the varying roles that Munich and Vienna play today in Europe's financial geography and elucidates to what extent this variation results from both longer-term and more recent developments.